2006
DOI: 10.1182/blood-2005-06-2269
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and complement-mediated lysis of myeloma cells by polyclonal rabbit antithymocyte globulin

Abstract: Current monoclonal antibody therapies for multiple myeloma have had limited success, perhaps due to narrow target specificity. We have previously described the ability of polyclonal rabbit antithymo-cyte globulin (rATG) to induce caspase-and cathepsin-mediated apoptosis in human B and plasma cells. We now extend this observation to myeloma cells. Complement independent cell death was measured after addition of rATG (1-1000 g/mL) to cultures of myeloma cell lines or primary CD138 isolates from patient bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 46 publications
3
65
1
Order By: Relevance
“…The cytotoxic effects of the Thymoglobulin on myeloma cells are also clearly observed in the absence of complement as in this study. [4][5][6] Importance of the caspases has been highlighted in a previous study where the cytotoxicity was significantly reduced in the presence of caspase inhibitors 5 and a second study that demonstrated activation of caspases 3, 8 and 9 in several myeloma cell lines. 6 The current study found that Thymoglobulin was able to induce apoptosis of myeloma cells resistant to conventional anti-myeloma agents, demonstrating non-overlapping mechanisms of action.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The cytotoxic effects of the Thymoglobulin on myeloma cells are also clearly observed in the absence of complement as in this study. [4][5][6] Importance of the caspases has been highlighted in a previous study where the cytotoxicity was significantly reduced in the presence of caspase inhibitors 5 and a second study that demonstrated activation of caspases 3, 8 and 9 in several myeloma cell lines. 6 The current study found that Thymoglobulin was able to induce apoptosis of myeloma cells resistant to conventional anti-myeloma agents, demonstrating non-overlapping mechanisms of action.…”
Section: Discussionmentioning
confidence: 98%
“…A role for complement has been suggested by previous studies that showed enhanced cytotoxicity of Thymoglobulin when cells are incubated in the presence of complement. 4,6 In addition, Zand et al 4 demonstrated decreased activity when cells were treated with the F(ab) 2 fragments instead of the whole antibody, an effect that was reversed by Fc ligation using other antibodies. The cytotoxic effects of the Thymoglobulin on myeloma cells are also clearly observed in the absence of complement as in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymoglobulin has broader activity on T-cell depletion, whereas ATG-Fresenius mainly Table 2 Allogeneic reduced-intensity conditioning after prior cytoreductive autograft (auto-allo approach) 39,40 More recently, ATG preparations as polyclonal antibody have shown in vitro complement-dependent and apoptosis-mediated cytotoxicity on myeloma cells. 41,42 Therefore, ATG might be able to improve remission rate after transplantation. However, the role of ATG in allogeneic stem cell transplantation of myeloma patients needs to be determined.…”
Section: Allo-sct In Myeloma N Krögermentioning
confidence: 99%
“…After binding to its targets, ATG mediates its cytotoxicity either through direct apoptosis via the Fas/FasL pathway, complement-dependent cytotoxicity (CDC), antibody-dependent cellular cytotoxicity (ADCC) by natural killer (NK) cells or neutrophils, and antibody-dependent cellular phagocytosis (ADCP) by monocytes and macrophages. [16][17][18][19][20] ATG affects early T-cell reconstitution by depleting graft-derived T cells that are important for T-cell recovery through homeostatic peripheral expansion. The CBgraft cells, most of which are naive, might contain more epitopes for ATG, which may make them more susceptible to ATG-mediated cytotoxicity than BM-graft cells.…”
Section: Introductionmentioning
confidence: 99%